Microplastics in oysters Saccostrea cucullata along the Pearl River Estuary, China. (May 2018) - Li, Heng-Xiang; Ma, Li-Sha; Lin, Lang; Ni, Zhi-Xin; Xu, Xiang-Rong; Shi, Hua-Hong; Yan, Yan; Zheng, Guang-Ming; Rittschof, Daniel
Abstract: As a transitional zone between riverine and marine environments, an estuary plays an important role for the sources, accumulation and transport of microplastics. Although estuarine environments are hotspots of microplastic pollution, the correlation between microplastic pollution and aquatic organisms is less known. Here we investigated microplastic pollution in wild oysters Saccostrea cucullata from 11 sampling sites along the Pearl River Estuary in South China. The microplastic abundances in oysters ranged from 1.4 to 7.0 items per individual or from 1.5 to 7.2 items per gram tissue wet weight, which were positively related to those in surrounding waters. The oysters near urban areas contained significantly more microplastics than those near rural areas. Fibers accounted for 69.4% of the total microplastics in oysters. Microplastic sizes varied from 20 to 5000 μm and 83.9% of which were less than 100 μm. Light color microplastics were significantly more common than dark color ones. Based on the results, oysters are recommended as a biomonitor for the microplastic pollution in estuaries. Graphical abstract: Image 1 Highlights: Microplastics were detected in all oyster samples collected from 11 sites along the Pearl River Estuary. Microplastics in oysters were positively related to the water they living in. The oysters near urban areas contained significantly more microplastics than those near rural areas. Fibers were the dominant microplastics in oysters.